Early Diagnosis of Bladder Exstrophy: Quantitative Assessment of a Low‐Inserted Umbilical Cord. (24th April 2017) - Fishel‐Bartal, Michal; Perlman, Sharon; Messing, Baruch; Bardin, Ron; Kivilevitch, Zvi; Achiron, Reuven; Gilboa, Yinon
Abstract : Objectives: Bladder exstrophy is a rare severe congenital malformation. Early prenatal diagnosis is scarcely described in the literature. Low insertion of the umbilical cord is a constant anatomic feature of bladder exstrophy. The aim of our study was to assess whether early measurements of the umbilical cord insertion–to–genital tubercle length may serve as quantitative measurements for a low‐inserted umbilical cord in cases of bladder exstrophy. Methods: The umbilical cord insertion–to–genital tubercle length was prospectively measured in all cases referred for a nonvisualized urinary bladder before 18 weeks' gestation. Final diagnoses were compared with prenatal measurements. Results: Fifteen fetuses were evaluated for a nonvisualized bladder at a mean gestational age of 15.7 weeks (range, 14–17 weeks). Of them, 6 cases were diagnosed with bladder exstrophy, and 9 cases had a normal urinary bladder. All cases with bladder exstrophy had an umbilical cord insertion–to–genital tubercle length below the fifth percentile for gestational age, whereas cases with a normal bladder had a normal measurement. Conclusions: Fetuses with bladder exstrophy have an umbilical cord insertion–to–genital tubercle length below the fifth percentile of the general population. This measurement may serve as a complementary objective sonographic parameter in the prenatal assessment and counseling of cases suspected of having bladder exstrophy during early pregnancy.